Competição de espécies daninhas com a cultura da soja: determinação do nível de dano e de parâmetros fisiológicos e bioquímicos associados - Salomão, Helis Marina (2022)
Competition is considered the main form of interference of weeds with cultivated species and, annually, causes high losses to world agriculture. It represents a form of mixed stress that causes large yield losses for crops. The responses of weed competition on morphological parameters and plant productivity are already well explored in the literature, however, there is still little information on its impact on metabolic variables of widely cultivated species. This justifies the relevance of further studies on this topic. Therefore, the objective of this work was to determine the effect caused by the interference of different densities of four weed species on biochemical, physiological and productive parameters of the soybean crop. Two field experiments were carried out in different locations during the 2020/2021 harvest. A randomized block design was used, with four replications, in a factorial scheme, having as the first factor the weed species (Euphorbia heterophylla, Ipomoea grandifolia and Urochloa plantaginea) and the second factor, the weed densities (0, 3 , 6, 12 and 24 plants per m2), in experimental units of 3.0 x 3.0 m. Cultivar 95Y92 was used, at a density of 300,000 seeds per hectare. In R5, plant height (AP), leaf area (AF), dry matter of leaves and stems (MSF and MSC, respectively) were evaluated in 10 plants per plot, and the chlorophyll content (Falker Index) and gas exchanges. Plant material was collected for analysis of proline, activity of superoxide dismutase, catalase and peroxidase enzymes, lipid peroxidation and solute extravasation, in addition to nutritional analysis. When the plants reached maturity, 10 plants were collected per plot to determine the yield components and the plants were harvested in the useful area of the plot to quantify productivity. Soybean plants in competition with I. grandifolia, E. heterophylla and U. plantaginea at increasing densities are negatively affected, with losses in morphological and physiological characters that fit the rectangular hyperbola model. The variables of AF, MSF, MSC and A are the ones that best explain the effects of the competitive process. As well, membrane integrity, lipid peroxidation and oxidative stress enzymes are the ones that best describe the attempts at metabolic defense of soybean plants. The competitive process developed differently, depending on the weed species studied. The results indicate that the determining factor of competition with I. grandifolia is the reduction of solar radiation interception. Higher soybean yield losses occurred in the presence of I. grandifolia, followed by U. plantaginea and E. heterophylla. The NCD, in the average of the two sites, was 54% for I. grandifolia, 29% for U. plantaginea and 26% for E. heterophylla. The number of pods per plant was the most affected soybean yield component by competition with weeds, being it correlated with the loss of productivity. Nitrogen was the element that presented the lowest levels in soybean leaf tissue, regardless of the weed in competition.